2022
DOI: 10.3390/app12094762
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Complexity of Knee Neuromuscular Control during an Isometric Task in Uninjured Physically Active Adults: A Secondary Analysis Exploring Right/Left and Dominant/Nondominant Asymmetry

Abstract: Work is needed to better understand the control of knee movement and knee health. Specifically, work is needed to further understand knee muscle force control variability and complexity and how it is organized on both sides of the body. The purpose of this study was to explore side-to-side comparisons of magnitude- and complexity-based measures of knee muscle force control to support future interpretations of complexity-based analyses and clinical reasoning in knee injury control. Participants (male/female n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Because physiological systems contain multiple anatomical components of different sizes, with each anatomical component containing physiological processes requiring different timeframes, a system's output (i.e., signal) is characterised by constant changes (i.e., fluctuations) across periods-of-time (Lipsitz and Goldberger, 1992). Therefore, quantifying muscle force signal fluctuations is Kandel ( 2013), Lephart et al (2000), Nowak et al (2013), Ostry and Feldman (2003), Pethick et al (2022a), , Williams et al (2001) needed to understand a person's neuromuscular control characteristics better (Clark and Pethick, 2022).…”
Section: Muscle Force Signal Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because physiological systems contain multiple anatomical components of different sizes, with each anatomical component containing physiological processes requiring different timeframes, a system's output (i.e., signal) is characterised by constant changes (i.e., fluctuations) across periods-of-time (Lipsitz and Goldberger, 1992). Therefore, quantifying muscle force signal fluctuations is Kandel ( 2013), Lephart et al (2000), Nowak et al (2013), Ostry and Feldman (2003), Pethick et al (2022a), , Williams et al (2001) needed to understand a person's neuromuscular control characteristics better (Clark and Pethick, 2022).…”
Section: Muscle Force Signal Constructionmentioning
confidence: 99%
“…Muscle force control is one representation of neuromuscular control (Clark and Pethick, 2022) (Table 1). The hardware and software used for measuring peripheral joint muscle force control have been described elsewhere by researchers working with healthy people (Pethick et al, 2015;Vaillancourt and Newell, 2003) and those with disease (Vaillancourt et al, 2001;Chow and Stokic, 2014) and injury (Skurvydas et al, 2011;Hollman et al, 2021).…”
Section: Muscle Force Control: Measurement Procedures and Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…For healthy individuals, Clark and Pethick [2] explored side-to-side comparisons (i.e., right/left and dominant/nondominant) of variability and complexity measures that potentially estimate knee muscle force control capabilities. The authors found that only right/left detrended fluctuation analysis (DFA) α, a nonlinear tool, indicated side-to-side difference in uninjured healthy people.…”
Section: Neuromechanical Estimation On Motor Functions In Specific Po...mentioning
confidence: 99%